Exploring the Impact of Mutation and Promotion on Career Development and Employee Performance at the Education and Culture Office - Maulida, Dina (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2023)
Improving employee performance in government agencies such as the education and culture office is an important element in efforts to provide quality public services. Mutation and promotion are two mechanisms that are often used in human resource management to optimize employee career development. This study aims to analyze and understand the effect of mutation and promotion on employee career development and its impact on employee performance at the Education and Culture Office. This study used a quantitative approach by collecting primary data through questionnaires distributed to a sample of employees at the Education and Culture Office. The data obtained were analyzed using descriptive statistical methods and regression analysis to assess the relationship between mutation, promotion, career development, and employee performance. The results of this study show that mutations and promotions have a significant influence on the career development of employees at the Education and Culture Office. The career development of employees, in turn, contributes positively to the improvement of their performance.